Casein phosphopeptides modulate calcium uptake and apoptosis in Caco2 cells through their interaction with the TRPV6 calcium channel - Silvia Perego; Alessandra Zabeo; Emiliano Marasco; Paola Giussani; Amelia Fiorilli; Guido Tettamanti; Anita Ferraretto (Journal of Functional Foods, 2013)
Dietary calcium intake is associated with colon cancer incidence due to its ability to modulate proliferation and apoptosis, cellular function directly linked to normal or tumour cell phenotype. In milk calcium is associated with casein whose hydrolysis produces the casein phosphopeptides (CPPs). CPPs induce calcium uptake in differentiated HT-29 and Caco2 cells. The aim of the present study was to explore: (i) the interaction between CPPs and the TRPV6 calcium channel in HT-29 and Caco2 cells; (ii) CPP effects on Caco2 cell functions. By reducing the expression of TRPV6 through small interfering RNA (siRNA), a decrease in cell response to CPPs was monitored in Caco2 cells (about 56%) but not in HT-29 cells. CPPs increased apoptosis both in undifferentiated and in transfected Caco2 cells. Based on the reported involvement of TRPV6 in cancer development, the results presented for CPPs may be helpful for their consideration as functional food ingredients.